2015
DOI: 10.1039/c4gc02175d
|View full text |Cite
|
Sign up to set email alerts
|

Pd embedded in chitosan microspheres as tunable soft-materials for Sonogashira cross-coupling in water–ethanol mixture

Abstract: Royal Society of ChemistryFrindy, S.; Primo Arnau, AM.; Lahcini, M.; Bousmina, M.; García Gómez, H.; El Kadib, A. (2015). Pd embedded in chitosan microspheres as tunable soft-materials for Sonogashira cross-coupling in water-ethanol mixture. Green Chemistry. 17(3):1893-1898. doi:10.1039/c4gc02175d. Pd Embedded in Chitosan Microspheres

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…The measured TOF value of 3097 ± 323 h −1 for heated (343 K) batch reaction mode is comparable with previously reported homogeneous ionic liquid catalysts (TOFs of 10 The palladium membrane loadings used for the Suzuki-Miyaura coupling reaction (a reaction solution equivalent of 0.061 ± 0.004 mol % or 11.1 ± 8 ppm on a mass basis) are lower than most previously reported ionic liquid catalysts (homogeneous and heterogeneous) which range between 0.1-18 mol% [5,[7][8][9][10][11][12][14][15][16]22,64]. A palladium leaching value of 83 ppb h −1 cm −3 at 343 K compares favourably with previously reported solid support heterogeneous catalysts (where palladium leaching rates exceed 100 ppb h −1 cm −3 ) [65,66]. This is equivalent to ∼1% of the Pd present leaching from an already sub 0.1 mol% catalyst during one reaction cycle at 343 K, and even lower leaching rates are to be expected when the membrane is used at room temperature.…”
Section: Discussionsupporting
confidence: 48%
“…The measured TOF value of 3097 ± 323 h −1 for heated (343 K) batch reaction mode is comparable with previously reported homogeneous ionic liquid catalysts (TOFs of 10 The palladium membrane loadings used for the Suzuki-Miyaura coupling reaction (a reaction solution equivalent of 0.061 ± 0.004 mol % or 11.1 ± 8 ppm on a mass basis) are lower than most previously reported ionic liquid catalysts (homogeneous and heterogeneous) which range between 0.1-18 mol% [5,[7][8][9][10][11][12][14][15][16]22,64]. A palladium leaching value of 83 ppb h −1 cm −3 at 343 K compares favourably with previously reported solid support heterogeneous catalysts (where palladium leaching rates exceed 100 ppb h −1 cm −3 ) [65,66]. This is equivalent to ∼1% of the Pd present leaching from an already sub 0.1 mol% catalyst during one reaction cycle at 343 K, and even lower leaching rates are to be expected when the membrane is used at room temperature.…”
Section: Discussionsupporting
confidence: 48%
“…Thiomers came into the research arena in the 1990s [10], and have since found multiple applications. For example, thiomers display a great cation binding capacity [48,49], demonstrated for metal ions such as Au(III), Pd(II), Pt(IV) [50], As(III), As(V) [51], Hg(II), Cu(II), and Ni(II) [52], as well as an efficient Pd carrier [53]. They are also of utility in the fabrication of colorimetric sensors for Hg 2+ detection at trace levels [54].…”
Section: Thiomers: Reactivity and Distinguished Propertiesmentioning
confidence: 99%
“…Other articles on cross‐coupling reactions using chitosan‐based palladium catalysts have been performed too. However, our paper presents a new modification which improves these methods …”
Section: Resultsmentioning
confidence: 99%